Baicalein and Baicalin Promote Melanoma Apoptosis and Senescence via Metabolic Inhibition - Huang, Lan; Peng, Bo; Nayak, Yash; Wang, Cindy; Si, Fusheng; Liu, Xia; Dou, Jie; Xu, Huaxi; Peng, Guangyong (Frontiers in Cell and Developmental Biology, 2020)
Malignant melanoma is one of the most common and dangerous skin cancers with a high rate of death every year. Furthermore, N-RAS and B-RAF mutations in melanoma cells increase the difficulties for clinical treatment in patients. Therefore, development of effective and universal drugs against melanoma is urgently needed. Here we demonstrate that baicalein and baicalin, the active components of the Chinese traditional medicinal plant Scutellaria baicalensis Georgi, can significantly inhibit melanoma cell growth and proliferation, suppress tumor cell colony formation and migration, as well as induce apoptosis and senescence in melanoma cells. The anti-tumor effects mediated by baicalein and baicalin are independent of N-RAS and B-RAF mutation statuses in melanoma cells. Mechanistically, we identify that the suppression of baicalein and baicalin on melanoma cells is due to inhibition of tumor cell glucose uptake and metabolism by affecting the mTOR-HIF-1a signaling pathway. In addition, we demonstrated that baicalein and baicalin can suppress tumorigenesis and tumor growth in vivo in the melanoma model. These studies clearly indicate that baicalein and baicalin can control tumor growth and development metabolically and have great potential as novel and universal drugs for melanoma therapy.